2022
DOI: 10.3102/00346543211070048
|View full text |Cite
|
Sign up to set email alerts
|

Equity and Social Justice in Research Practice Partnerships in the United States

Abstract: Research–practice partnerships (RPPs) have grown rapidly in the last decade in the United States to challenge traditional notions of education research by emphasizing the importance of researchers and practitioners working together in a spirit of mutuality to develop research questions, collect data, implement interventions, and analyze and use findings. RPP scholarship in the United States has historically advocated for the need to pay more focused attention to issues of equity and justice. To address that ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…In essence, the definition of equity in RPPs becomes another example of how negotiating identity, values, and priorities within an RPP is an inherently political process. Similar to other literature (e.g., Vetter et al, 2022), Farrell, Singleton et al (2022 share a framework for thinking about what equity in RPPs looks like-both in terms of what RPPs do ("equity-in-mission") and how they do it ("equity-in-process")-to aid in developing common language and to guide future research.…”
Section: Politics Of Addressing Equity and Transformation In Rppsmentioning
confidence: 87%
“…In essence, the definition of equity in RPPs becomes another example of how negotiating identity, values, and priorities within an RPP is an inherently political process. Similar to other literature (e.g., Vetter et al, 2022), Farrell, Singleton et al (2022 share a framework for thinking about what equity in RPPs looks like-both in terms of what RPPs do ("equity-in-mission") and how they do it ("equity-in-process")-to aid in developing common language and to guide future research.…”
Section: Politics Of Addressing Equity and Transformation In Rppsmentioning
confidence: 87%
“…We do not assume we have gained school members’ trust simply because we have established the partnership; rather, we set aside time for what ORJ staff have called structured and unstructured dialog, listen to the needs and stories of our partner schools, model vulnerability, and provide space to make mistakes while holding each other accountable. Similar to other partnerships, this form of relationship building sets the foundation for our future joint work (Vetter et al, 2022), but in racial justice work, it also allows partners to engage in conversations about racial harm and healing. One school leader commented, “[Our ORJ facilitator] did a lot of great work around facilitating issues that came up along the year within the equity committee group, and within the school community.…”
Section: Partnerships In Pursuit Of Racial Justice: Lessons From the ...mentioning
confidence: 99%
“…During the initial stages of the work, we have also learned to talk more explicitly about our processes and values up front (Farrell et al, 2019; Vetter et al, 2022). Many school leaders are not fully aware of the challenges inherent in pursuing racial justice work (Gorski, 2019; Lewis & Diamond, 2015).…”
Section: Partnerships In Pursuit Of Racial Justice: Lessons From the ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This research gap calls into question the power dynamics of RPPs, including whether researchers see themselves as equal learners and whether the partnerships are designed in equitable and anti-racist ways that equally value the knowledge and skills of all partners (see Wilson, 2021). As Vetter et al, (2022) point out, for RPPs to advance equity and social justice they must intentionally center equity and justice in planning and design, attend to historical power relationships and acknowledge power differences, and specifically investigate and address inequities in problems of practice. This type of centering is quite uncommon—in fact, they found that only about 10% of the publications they reviewed described RPPs that were equity focused—suggesting an important area of focus for those engaged in developing and studying RPPs.…”
Section: Political Dynamics and Social Contextsmentioning
confidence: 99%